Fast examination and interventional ultrasound in the diagnosis and treatment of combat abdominal trauma - Kashtalian, M.; Herasymenko, O.; Haida, Ya.; Shkliarevych, P.; Atanasov, D.; Okolets, A. (Journal of Education, Health and Sport, 2023)
To improve the diagnosis and surgical treatment of wounded patients with combat abdominal trauma by methods of emergency ultrasound diagnostics and minimally invasive surgery under the control of ultrasound. The purpose of the work is to improve the results of diagnosis and surgical treatment of wounded patients with combat abdominal trauma by emergency ultrasound examination techniques and minimally invasive surgical interventions under ultrasound control. A clinical and statistical analysis of the results of the surgical treatment of 293 wounded patients with combat abdominal trauma treated at the Military Medical Clinical Centre of the Southern Region was conducted. In the main group, additional therapeutic and diagnostic measures were performed — focused assessment with sonography in trauma (FAST), puncture rehabilitation and drainage surgery under the control of ultrasound. In the main group, in contrast to the control group, FAST examination was conducted in all wounded patients. The widespread introduction of the FAST examination and diagnostic punctures under ultrasound control into diagnostics reduces the level of more traumatic diagnostic laparocentesis from 24.7 to 2.2% and unreasonable surgical interventions from 3.2 to 0.7 %. An algorithm of diagnostic and therapeutic measures for wounded patients with combat abdominal trauma based on the results of the FAST examination was developed. The data obtained indicate that the widespread implementation of FAST, percutaneous puncture and sanitation interventions under ultrasound control in the diagnosis and treatment of combat abdominal trauma and its complications helps to reduce the number of invasive and more traumatic (often useless) interventions, which leads to faster recovery and shorter treatment time.